Development of technology for omega enriched mixed fat spread: Omega enriched mixed fat spread - Hamid, Aliasgar; Gokhale, Ajay; Dharaiya, Chetan N; Kumar, Aditya; Parmar, Satish (Indian Journal of Dairy Science, 2025)
This study aimed to develop an omega-enriched fat spread with improved nutritional benefits. Response surface methodology (RSM) was employed to optimize the levels of total fat, omega fat (combination of sesame oil and flaxseed oil) and diacetyl (flavour ingredient) in the fat spread. The results showed that the flavour score was mainly influenced by total fat and diacetyl content. The body and texture score increased with the addition of omega fat but decreased with increasing total fat. The colour and appearance score was not significantly affected by the any variables. Spreadability score decreased with lower omega fat and higher total fat content. Overall acceptability score was positively influenced by diacetyl content but negatively influenced by total fat content. The optimized product contained 53.4% total fat, 16.6% omega fat and 2.5 ppm diacetyl, exhibited desirable physico-chemical attributes, acceptable sensory properties, superior spreadability and a favourable fatty acid profile. Optimized product had 700 per cent more omega-6 and 1700 per cent more omega-3 fatty acids as compared to control fat spread and omega-6 to omega-3 fatty acids below 5:1.